Peran Guru dalam Mengatasi Kesulitan Membaca dan Menulis pada Siswa Sekolah Dasar dengan Hambatan Intelektual: The Role of Teachers in Overcoming Reading and Writing Difficulties in Elementary School Students with Intellectual Disabilities - Sartika Sari Sinaga; Veronika Banjarnahor; Esra Theresia Sinambela (ITScience (Information Technology and Science), 2025)
Education at the elementary school level is a crucial stage for children to recognize and understand letter symbols as a basis for reading and writing. For this reason, reading and writing skills are closely related to a person's language or communication skills in their social environment. The role of teachers in providing services for students with intellectual disabilities in reading and writing is not only as an educator but also as a facilitator and motivators in helping students achieve their best potential. This study uses literature study research by analyzing by comparing the results of previous studies through journals that are relevant to the study of the problems being studied. Language in social communication (the relationship between language, society, and ecology) Students in schools more often use regional languages, namely Malay, in communicating both during learning in the classroom and the school environment. This habit causes students' Indonesian language vocabulary to be lacking, impacting the following lessons. This can be seen in students who have difficulty understanding interactive communication during the learning process even though they use Indonesian and understand the contents of the reading. The impact of this difficulty is that students' learning achievements are often below the KKM. This student does not understand the punctuation in a text, writes irregularly, is not fluent in reading, and even has difficulty communicating with his interlocutor. The role of teachers can overcome the difficulties of students who experience intellectual barriers academically in reading and writing at SDN 004 Teluk Durian Elementary School by implementing various strategies and appropriate approaches.